(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This Paper analyzed the effectson magnetic field of an incompressible viscous fluid past a porous plate i.e.the fluid is electrically conducting, the effects of the porosity of themedium, the surface stretching velocity, The heat generation coefficient onboth the flow and heat transfer are presented. A numerical solution for thegoverning nonlinear momentum and energy equations is obtained.